Masifnya Penggunaan Online Travel Agents Dalam Meningkatkan Revenue Pemasaran - Istikhomah Istikhomah; Gede Sri Darma (Universitas Pendidikan Nasional, 2016)
Marketing Strategy Concept E-Marketing is based Online Travel Agents (OTA). Online travelagents are travel agents that make media promotion and online sales through a website.Today almost all companies have a website for the promotion of products to consumers.Various advantages of using e-marketing strategy is not in doubt, the Internet has changedthe practice of marketing. Developments in information technology resulted in thetransformation of marketing and provide modern marketing channels that drive change in theconventional communication towards digital communications.Gains from sales promotion via OTA (Online Travel Agents), data occupancy rate InnaSindhu Beach in 2015 showed that 50% of them are reservations through online travelagents, 30% through offline travel agents, and 20% a reservation directly via email or phone.This shows that online travel agents is a medium that is able to significantly increase the levelof occupancy hotels and in terms of saving time because it is not necessary sales calls. Hardlyany losses cooperate with Online Travel Agents (OTA) because the registration andpromotion is free. Another advantage experienced is if the guest is satisfied with the serviceshotel, the guest has the potential to become a repeater guest and implications for the positiveword of mouth.Keywords : Marketing Strategy, E-Marketing, Online Travel Agents (OTA).